Cuidado de la salud mental del personal de salud durante COVID-19: recomendaciones basadas en evidencia y consenso de expertos - Cantor-Cruz, Francy (Rev Colomb Psiquiatr, 2021)
INTRODUCTION: The crisis situation generated by COVID-19 and the measures adopted have generated social changes in the normal dynamics of the general population and especially for health workers, who find themselves caring for patients with suspected or confirmed infection. Recent studies have detected in them depression and anxiety symptoms and burnout syndrome, with personal and social conditions impacting their response capacity during the health emergency. Our aim was to generate recommendations for the promotion and protection of the mental health of health workers and teams in the first line of care in the health emergency due to COVID-19. METHODS: A rapid literature search was carried out in PubMed and Google Scholar, and an iterative expert consensus and through electronic consultation, with 13 participants from the areas of psychology, psychiatry and medicine; the grading of its strength and directionality was carried out according to the international standards of the Joanna Briggs Institute. RESULTS: Thirty-one recommendations were generated on self-care of health workers, community care among health teams, screening for alarm signs in mental health and for health institutions. CONCLUSIONS: The promotion and protection activities in mental health to face the health emergency generated by COVID-19 worldwide can include coordinated actions between workers, health teams and health institutions as part of a comprehensive, community care, co-responsible and sustained over time.